"Sorry, Darling": Apologizing in The Crown TV Series - Pradhana Ahmad Maulana; Tofan Dwi Hardjanto (Lexicon, 2019)
The present research investigates the realization of apologies in the TV series entitled The Crown. In doing so, the study attempts to identify and classify apology strategies employed by the characters in the series using the taxonomy proposed by Blum-Kulka and Olshtain (1984). The collection of the apology data was done through observation of the series, starting from the first episode in the first season to the twentieth episode in the second season. The investigation has successfully identified and classified 45 apologies. From a total of 45 apologies found, 33 (73.4%) were classified as direct realizations (27 or 60% as standalone IFIDs and 6 or 13.3% as IFID combinations). Indirect apology realizations, however, were relatively rare with only 12 (26.6%) occurrences in total. The explanation of situation was found to be the most commonly used indirect strategy with six (13.3%) instances. The results seem to suggest that the characters in the series prefer direct strategies in apologizing in English.